Late-onset cobalamin C deficiency type in adult with cognitive and behavioral disturbances and significant cortical atrophy and cerebellar damage in the MRI: a case report - Sun, Miao; Dai, Yingjie (Frontiers in Neurology, 2023)
Late-onset cobalamin C (cblC) deficiency is associated with a wide range of neurological and psychiatric symptoms, hematological manifestations, anorexia, renal failure, ocular abnormalities, dermatitis, and pancreatitis. However, the neuroimaging characteristics of late-onset cblC deficiency remain insufficiently documented. Common findings include diffuse white matter swelling, varying degrees of severe leukoaraiosis, hydrocephalus, corpus callosum atrophy, and symmetric bilateral basal ganglia lesions. In this report, we present a case of late-onset cblC deficiency in adults presenting with cerebellar ataxia as the primary symptom. The MRI findings revealed bilateral lateral cerebellar hemispheres exhibiting symmetric hyperintensity, primarily observed in diffusion-weighted imaging (DWI), which is a rarely reported imaging change in this context.Our patient was a male who experienced symptoms starting at the age of 30 years, including unsteady walking, apparent cerebellar